HUBUNGAN KECERDASAN EMOSIONAL DENGAN KOMPETENSI PROFESIONAL GURU TK KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Maulidatul Istiqomah; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to know whether there is levels and correlation between emotional intelligence and professional competency teacher kinder garden in kecamatan tanah putih kabupaten rokan hilir. The population of this research is the teacher kinder garden Kecamatan Tanah Putih Kabupaten Rokan Hilir that consist of 205 teacher, the sample of research are 67 teacher. Method of this research is Pearson Product Moment correlation to know the correlation between Emotional Intelligence and Professional Competence. The technique of collecting data used questioner in Likert scale from. The technique of analyzing data used scale test and statistic analytical by using SPSS program of Windows ver. 17. Based of this research there is level of emotional intelligence in the medium category with the percentage 78.02% and the level of professional competency in the medium category with the percentage 77.04%. Based of hypothesis there is any significant positive correlation between emotional intelligence and professional competency teacher kinder garden in Kecamatan Tanah Putih Kabupaten Rokan Hilir. It could be seen from the result of correlation coefficient that rxy = 0.636 and significant level is 0.000 0.05. the level of correlation between emotional intelligence and professional competency of teacher in the middle with the rank of determinant coefficient in the amount of KD =r2 x 100% = 40.5%, it means that emotional intelligence affect professional competency as much as 40.5%.Key Words: Emotional Intelligence, Professional Kompetency.